Interaksi Sosial Akun Twitter PT.Angkasa Pura II (Studi Analisis Isi) - Tsaniyah, Nadhifah Bernice; Putri, Nabila Aulia Rahma; Kafidani, Hana Naura; Amalia, Diana (Lembaga Yasin AlSys, 2024)
Social interaction is a reciprocal relationship between individuals that mutually influences each other. Social interaction not only occurs in the real world but can also take place on social media accounts. Social media interactions happen when users engage with each other through available platforms. Social media provides convenience for users to interact with friends, family, and even distant relatives through the provided social media accounts without the need for face- to-face meetings. Our research aims to analyze the content posted by the Twitter account of PT. Angkasa Pura 2. This includes the types of posts, discussed topics, and how the content relates to the organization's communication goals. The research method used is descriptive research. Descriptive research employs an approach that is used to depict and define the characteristics of a phenomenon without making changes to it. This study will uncover and understand the root issues of